THE ANALYSIS OF CONSUMER PERCEPTION TOWARDS CHINESE PRODUCTS IN MANADO - Watung, Edward Chandra (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Product is one of the marketing tools, and something that marketers offer to market, which the target is to meet the consumer needs and wants. China becomes one of the largest countries that produced many products. Many of the Chinese products enter the market almost around the world. This research is conduct in Manado, North Sulawesi. The objectives of this research are to analyze consumer perception towards Chinese products, partially and simultaneously. This research is the causal type of research where it will investigate the influence of elements on consumer perception. Use multiple regression models to answer the research problem. The population in this study is a consumers of Chinese products, whereas samples taken by each respondent 100 respondents. The hypothesis testing, this research conduct a conclusion of there is a significant influence of Country of Origin, Product Quality, Product Type, and Price Sensitivity simultaneously and there is a significant influence of Product Type and Price Sensitivity partially on Consumer Perception. This study reveals that price sensitivity is a mental decision that made by the consumer has a strong influence factor in order to buy a product, when consumer go for purchasing, they prefer to purchase a product with affordable price. Keywords: consumer perception, product type, price sensitivity.